Exploring the Role of Adipose Tissue Dysregulation in Vitiligo Pathogenesis: A Body Composition Analysis - Shao, XinYi; Pan, Xingyu; Chen, Tingqiao; Chen, Ziyan; Li, Yuhao; Zhong, Judan; Wang, Ruiyao; Yu, Jun; Chen, Jin; Chen, Yangmei (Acta dermato-venereologica, 2024)
Vitiligo is a commonly acquired pigmentary disease characterized by the progressive destruction of melanocytes. The role of adipose tissue in vitiligo remains unclear. To investigate the role of adipose tissue in the pathogenesis of vitiligo, 50 patients newly diagnosed with vitiligo and 40 age- and sex-matched healthy controls were enrolled, and fat mass and distribution using dual-energy X-ray absorptiometry (DXA) and serum adipokine levels using enzyme-linked immunosorbent assay were assessed. The trunk and whole-body fat mass and the trunk/limb fat mass ratio were significantly higher in patients with vitiligo. Higher leptin and resistin levels and lower adiponectin levels were observed. Positive correlation of the trunk fat mass index with vitiligo area scoring index scores (r = 0.38, p = 0.0071) was found. Additionally, plasma adiponectin levels were negatively correlated with vitiligo disease activity scores (r = –0.307, p < 0.05). Receiver operating characteristic curve analysis showed that the percentage of limb lean tissue mass, trunk/limb fat mass ratio, and serum adipokine levels achieved a high area under the curve score for distinguishing patients with vitiligo from healthy controls. In conclusion, the incidence of central obesity and adipokine dysregulation was higher in patients with vitiligo. The potential role of adipose tissue in the pathogenesis of vitiligo should be emphasized.